SISTEM INFORMASI AKUNTANSI DALAM AUDIT PENGENDALIAN INTERNAL BERBASIS KOMPUTER - Dita Dwi Khoirir Roziq; Ely Setyawati, Charisma Wulandari, Noor Fadilatus Sakdiyya, Yuni Sukandani (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
This study discusses the accounting information system in computer-based internal audit control. The purpose of this study is to determine and analyze the accounting information system in computer-based internal audit control. The research method uses a descriptive qualitative method. Data analysis is carried out by data reduction, data interpretation and drawing conclusions. The results of this study are that a sophisticated modern computerized Accounting Information System is achieved without reliable internal management system control such as strict supervision by expert management in their fields, internal control can effectively affect the accounting information system Information and communication are important elements of computer-based internal control, usually control that is usually done by humans has been replaced by machines whose role is very important in the company